Here comes Mr. Jordan [videorecording (DVD)] - Buchman, Sidney, 1902-1975; Miller, Seton I.; Walker, Joseph B.; Hollaender, Friedrich; Head, Edith; Montgomery, Robert, 1904-1981; Rains, Claude, 1889-1967; Keyes, Evelyn, 1916-2008; Gleason, James, 1886-1959; Horton, Edward Everett; Johnson, Rita, 1912-1965; Emery, John, 1905-1964; et al. (Criterion collection, 2016)
Boxer Joe Pendleton dies 50 years too soon due to a heavenly mistake, and is given a new life as a millionaire playboy.